Integrating water availability for electrolysis into energy system modeling - Julian Walter; Lina Fischer; Sandra Venghaus; Albert Moser (Advances in Applied Energy)
In recent years, temperature records have been broken all over the world and the global temperature keeps rising. As a result, fresh water availability will diminish ever more and more due to droughts and extreme weather events. Water is a key part of many central aspects of life but will also become important in the future for electrolysis to synthesize hydrogen, a promising energy carrier in energy systems for the transition from fossil to renewable energy. Current energy system optimization models neglect water as an input for electrolysis when focusing on electricity. In this study, we present a method for implementing water as an input in energy system optimization models, with constraints for freshwater availability and seawater processing. We apply our method to one scenario and investigate the impact on the European energy system with highly-detailed spatial and temporal resolutions. The results indicate a relocation of electrolysis capacities of 10% and an increase of methane imports and methanation capacities. The effects suggest that water should be considered in energy system optimization in the future.